2020
DOI: 10.1177/1457496920964337
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment is effective in treating thymoma accompanied with non-myasthenia gravis autoimmune diseases: a single-center clinical experience

Abstract: Background and Aims: Although thymoma is inextricably linked to autoimmune disease, its best treatment method remains unclear. In this study, we sought to evaluate therapeutic effect of surgical resection of thymoma on non-myasthenia gravis autoimmune diseases. Materials and Methods: This was a retrospective study covering 32 patients with thymoma accompanied with non-myasthenia gravis autoimmune disease. The relationships between surgical treatment, thymoma pathological type, and prognosis of autoimmune disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In addition, immune disease-related words such as systemic-lupus-erythematosus, lichen-planus, t-cells, and red-cell aplasia also appeared in the top 100 keywords, and according to VOSviewer cluster analysis, the frequency of such words has gradually increased in recent years. Our team has also found that surgery has a certain effect on treating non-myasthenia Gravis autoimmune diseases [21]. Similarly, laboratory research on thymoma has gradually increased in recent years, and since 2000, the number of highly cited laboratory studies on thymoma has gradually increased.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, immune disease-related words such as systemic-lupus-erythematosus, lichen-planus, t-cells, and red-cell aplasia also appeared in the top 100 keywords, and according to VOSviewer cluster analysis, the frequency of such words has gradually increased in recent years. Our team has also found that surgery has a certain effect on treating non-myasthenia Gravis autoimmune diseases [21]. Similarly, laboratory research on thymoma has gradually increased in recent years, and since 2000, the number of highly cited laboratory studies on thymoma has gradually increased.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that many autoimmune diseases, such as Hashimoto's thyroiditis, Isaac's syndrome, and Morvan syndrome were caused by thymoma (9). Sometimes, surgical treatment might result in good prognosis of thymoma combined with nonmyasthenia gravis autoimmune diseases (10)(11)(12)(13). Here, we report the clinical and genetic characteristics of 13 special thymoma patients with autoimmune hepatitis and myocarditis.…”
Section: Discussionmentioning
confidence: 89%
“…Paraneoplastic psoriasis has only been described in a couple of cases regarding thymic tumors [ 7 - 8 ]. The prototypical paraneoplastic syndrome associated with thymoma is myasthenia gravis (MG), with occurrence of 30%-50% in thymoma patients generally [ 9 ].…”
Section: Discussionmentioning
confidence: 99%